Effect of large thickness-reduction on microstructure evolution and tensile properties of Mg-9Al-1Zn alloy processed by hard-plate rolling. (20th October 2021) - Li, Yong-Kang; Zha, Min; Rong, Jian; Jia, Hai-long; Jin, Zhong-Zheng; Zhang, Hong-Min; Ma, Pin-Kui; Xu, Hong; Feng, Ting-Ting; Wang, Hui-Yuan
Graphical abstract: Highlights: The volume fraction and size of fine grains in bimodal-grained AZ91 alloy were manipulated by hard-plate rolling (HPR). The optimized bimodal grain structure accounts for AZ91 alloy having a superior combination of ductility and strength. Underlying mechanisms for improved strength and ductility in optimized bimodal AZ91 were discussed. Abstract: The effect of large thickness-reduction on microstructure evolution and tensile properties of Mg-9Al-1Zn alloy (AZ91) processed by hard-plate rolling (HPR) was investigated. Increasing rolling reduction from 55 % to 85 % increases the volume fraction and refines average size of fine grains (< 3 μm, FGs), leading to an optimized bimodal-grained structure consisting of coarse grains (CGs) uniformly embedded in FG regions. The sample with 85 % reduction exhibits the highest yield strength of ∼314 MPa, ultimate tensile strength of ∼381 MPa and elongation of ∼11 %. The high strength is primarily due to the contribution of grain boundaries (GBs) strengthening by FGs (accounting for ∼65 % of strength), meanwhile the improved ductility originates from the optimized bimodal-grained structure and weakened basal texture that favor a higher ductility. The present findings successfully overcome the trade-off dilemma that the large-reduction rolling processing on Mg alloys usually enhances strength at expense of ductility. In addition, the intensified heterogeneous deformation and favorable formation of a bimodal-grained microstructure during large-reduction HPR was addressed by tracing microstructure evolution details in grains of interest via quasi-in-situ electron back scattering diffraction (EBSD). The present study can be instructive for further designing novel Mg alloys by tailoring bimodal-grained structures for superior combination of mechanical properties.